Detection of transmissible viral proventriculitis and chicken proventricular necrosis virus in the UK. Issue 1 (2nd January 2017) - Grau-Roma, Llorenç; Reid, Kirsty; de Brot, Simone; Jennison, Richard; Barrow, Paul; Sánchez, Raúl; Nofrarías, Miquel; Clark, Mike; Majó, Natàlia
ABSTRACT: Increasing evidence suggests that a new birnavirus, named chicken proventricular necrosis virus (CPNV), is the aetiological agent of transmissible viral proventriculitis (TVP). The present work aimed to explore the possible presence of both TVP and CPNV in the UK. Forty-four chickens showing TVP-compatible gross lesions were classified into three groups based on the histological lesions: (i) TVP-affected chickens: lymphocytic infiltration and glandular necrosis ( n = 15); (ii) lymphocytic proventriculitis (LP)-affected chickens: lymphocytic infiltration without necrosis ( n = 18); and (iii) without proventriculitis (WP): no lymphocytic infiltration or necrosis ( n = 11). Nine proventriculi (seven out of 15 corresponding to TVP, and two out of 11 corresponding to LP) were positive for CPNV by reverse transcriptase polymerase chain reaction (RT-PCR). These results support the previously suggested idea of CPNV as causative agent of TVP. Moreover, these data show that CPNV can also be detected in a number of cases with LP, which do not fulfil the histological TVP criteria. Phylogenetic analysis of partial sequences of gene VP1 showed that British CPNV sequences were closer to other European CPNV sequences and might constitute a different lineage from the American CPNV. TVP cases with negative CPNV PCR results may be due to chronic stages of the disease or to the reduced PCR sensitivity on formalin-fixed paraffin-embedded tissues. However, involvement of other agents in some of the cases cannot totally be ruled out. As far as the authors are aware, this is the first peer-reviewed report of TVP as well as of CPNV in the UK, and the first exploratory CPNV phylogenetic study.